Unraveling the scales of effect of landscape structure on primate species richness and density of titi monkeys (Callicebus nigrifrons) - Gestich, Carla C.; Arroyo-Rodríguez, Víctor; Ribeiro, Milton C. [UNESP]; da Cunha, Rogério G. T.; Setz, Eleonore Z. F. (Wiley, 2019)
In the Anthropocene, many animal populations are increasingly confined to human-modified landscapes, in which different spatial variables describing landscape composition and configuration influence species persistence. Forest specialist species are particularly vulnerable to these landscape disturbances. Yet, landscape effects may be undetected if assessed at the wrong spatial scale. Thus, identifying the “scale of effect”, which is the optimal spatial scale for estimating ecological responses to each landscape variable, is needed to understand the impact of landscape structure modification on species. Here, we explored the scale of effect of two compositional (forest cover and anthropogenic cover) and two configurational landscape variables (forest patch density and forest edge density) on two ecological responses: primate species richness and group densities of titi monkeys (Callicebus nigrifrons). We sampled 16 study sites in northeastern São Paulo State, Brazil. For each site, we measured each landscape variable within 10 different-sized landscapes ranging from 0.2 to 28.3 km 2 to identify the scale of effect of each landscape variable. The strength of all the primate-landscape relationships varied across spatial scales. Although both ecological responses were most strongly associated with forest cover at the largest scale, the scale of effect of the other landscape variables differed between the response variables. These results suggest that each response variable is shaped by landscape patterns and processes operating across different spatial scales. We highlight the importance of separately assessing the scale of effect of each landscape variable on each ecological response to better understand the impact of landscape structure on species persistence.
Keywords: landscape approach; multiscale assessment; population density; primate community; scale of effect